Challenging Experiences of the Fathers of the Premature Infants Admitted in the Neonatal Intensive Care Unit (NICU) - Zahra Shahkolahi; Zahra Mahdavi Lenji; Soheila Jafari-Mianaei (Mashhad University of Medical Sciences, 2018)
Background: Birth of premature infants and their admission in the neonatal intensive care unit (NICU) are unexpected crises for the fathers. Therefore, raising the awareness of fathers regarding their experiences in such conditions could be helpful in the care of these neonates. The present study aimed to investigate the experiences of the fathers of the premature infants admitted in the NICU. Methods: This descriptive, explorative, qualitative study was conducted via purposive sampling, and 13 parents of the premature infants admitted in the NICUs of two hospitals in Isfahan, Iran, were enrolled. Semi-structural interviews were performed with the fathers of premature infants, and thematic analysis was used for data analysis. Results: Three main themes emerged in the study, including 'emotions and responsibilities', 'information needs', and 'beliefs'. In terms of the emotions and responsibilities, fear and accountability were considered to be the major concerns among the fathers. With regard to information needs and beliefs, the need to obtain appropriate information and having faith in God and the infallible Imams were expressed by the fathers, respectively. Conclusion: Experiencing preterm birth and NICU admission are accompanied by stress and anxiety for the parents of the infants. Meanwhile, several factors could impair the ability of the fathers to cope with the crisis. Identifying and addressing the needs of the parents and providing the necessary training since the beginning of pregnancy could result in the effective management of NICU admission. In addition, proper facilities should be offered to support the fathers of preterm infants, such as parental leave.